P63 Mechanisms of Action of PLasma Exchange (MAPLE) – an exploratory proteomic analysis. (20th September 2022) - Burke, Laura; Jauniaux, Benoit; Banks, Rosamonde; Karakantza, Marina; Kerr, Maria; Moore, Joanna
Abstract : Plasma exchange (PEX) has shown promising results in improving transplant free survival in patients with acute liver failure (ALF). 1 The specific mechanism of action is not understood. The hypothesis that multi organ failure (MOF) in patients with ALF is due to an overwhelming immune response would suggest that the role of PEX is multifaceted; replacing circulating proteins normally produced by the failing liver and removing pro-inflammatory cytokines, thus modulating the immune response. In this prospective pilot exploratory study we aimed to utilise proteomics technologies to explore and quantify the systemic changes induced by PEX on circulating proteins in patients with ALF to provide insight into mechanisms underlying the benefit of this therapy. Patients with ALF due to paracetamol overdose receiving PEX between June 2019 – August 2020 were enrolled. Plasma samples were taken at multiple time points across PEX cycles. Samples from healthy controls (HC), Octaplas batches and patients with ALF receiving standard medical treatment (SMT) were collected for comparison. Samples were analysed on 2 (inflammation and cardiometabolic) Olink Target panels. Quantification was relative allowing comparison across samples. Initial data exploration was undertaken using principal components analysis (PCA) of baseline samples. Profiles were examined for longitudinal patterns, focussing on proteins in PEX cohort that differed in concentration by at least 2 fold at baseline compared with HC. 56 samples were analysed: Octaplas n=8, HC n=7, ALF SMT n=8 (4 patients sampled at baseline and 24 hrs later) and 33 longitudinal samples from 4 ALF-PEX patients ( table 1 ). 184 proteins were measured on the two arrays. Marked differences were seen in the total protein concentration at baseline across cohorts (Image 1). Distinct patterns of response to PEX cycles were seen: 1) Protein concentration high at baseline and decreased towards HC e.g. IL 6, superoxide dismutase, Caspase 8 ( figure 1 ) 2) Protein concentration low at baseline and increased towards HC e.g. Mannose binding protein 3, Apolipoprotein M and Insulin like growth factor binding protein 3 3) Protein concentration high at baseline and increased further away from HC e.g. Regenerating islet−derived protein 3−alpha In this first proteomic analysis of patients undergoing PEX for ALF we have comprehensively demonstrated distinct changes in circulating proteins. The longitudinal change seen in protein concentrations augment the current understanding of PEX mechanism of action and identifies proteins for further exploration of their biomarker potential.